Dental practice in Europe at the end of the 18th century - Hillam, Christine (Wellcome series in the history of medicine., 2004)
Here is presented for the first time an overview of dental practice and the providers of dental treatment at the close of the eighteenth century in some of the major countries of western Europe and further afield. It draws on previously under-explored primary sources, rigorously referenced, and enables comparison of and contrast within the emergent specialty in rapidly-changing social and political environments. The overall picture challenges conventional wisdom and will be of interest to social as well as to dental and medical historians.